Understanding food safety awareness and practices along smallholder pig value chains in Vietnam using participatory approaches - Sinh Dang Xuan; Unger, Fred; Hung Nguyen-Viet; Fries, R.; Phuc Pham Duc; Meeyam, T. (International Livestock Research Institute, 2015)
Pig production plays an important role in both food supply and economic development in Vietnam. We assessed the food safety awareness and practice of involved key actors along the smallholder pig value chains in Hung Yen, Vietnam using participatory approaches. Data collection included quantitative (checklists, questionnaires) and qualitative (in-depth interviews and focus group discussions-FGD) tools and was done in three districts of Hung Yen. All survey tools were developed and pre-tested. Checklists (n=22) and questionnaires (n=12) followed random sampling procedures. The respondents for in-depth interviews (n=24) were randomly selected, while the participants for FGDs (n=5) were recruited by convenience. Data collection was done between January and June, 2013. Descriptive statistic was used for quantitative data, while content analysis was used for qualitative data. The outline for data collection for included groups and stakeholders (slaughterhouse workers, pork sellers, veterinary and public health staff, people living around slaughterhouses, pork consumers) was structured around food safety, diseases and health risks. Differences in what some groups found important or unsafe, based on their occupational priorities or labour focus were identified by using ranking tables and analysed accordingly. Analyses show that for slaughterhouse workers and pork sellers the food safety risks were highest and linked to lack of training, or relying only on “learning by doing” an experience provided by other workers or sellers. People living around slaughterhouses expressed concerns about health effects but also pointed out the advantages of their proximity to slaughterhouses, such as job opportunities and easy access to fresh pork. Pork consumer groups were more concerned about sensorial criteria (e.g. freshly looking, bright red colour) and expressed also some awareness on pork quality. Veterinary and public health staff emphasised the gap between existing legislation and food safety practices. Findings provide information on food safety awareness and practices along various actors and stakeholders. There is a need for improved standards, targeted training and collaborative mechanisms between veterinary and public health authorities to better manage the food production chain.